1987
DOI: 10.1111/j.1432-1033.1987.tb13717.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial peptide inactivation by rabbit‐kidney brush‐border membranes

Abstract: Atriopeptin (AP) 24, containing amino acids Serlo3 -Tyr126 of the carboxy-terminal portion of the atrial natriuretic peptide prohormone, was degraded rapidly by rabbit kidney brush border membranes. The rate of degradation of AP24 measured by the loss of vasorelaxant activity followed a similar time course to the decrease in peptide peak area measured by high-performance liquid chromatography. Inactivation of AP24 produced peptide fragments which were separated by HPLC. The major products were purified individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Furthermore, following incubation for 4 h, the degradation of 125 I-labeled DNP remained attenuated by phenanthroline. The present findings are consistent with previous studies (17,18) and indicate the significance of NEP in the inactivation of DNP, similar to ANP, revealing that NEP is involved in the inactivation of BNP and ANP in the plasma. However, these observations are fairly different from an earlier study, which revealed that DNP was resistant to degradation by NEP (29).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, following incubation for 4 h, the degradation of 125 I-labeled DNP remained attenuated by phenanthroline. The present findings are consistent with previous studies (17,18) and indicate the significance of NEP in the inactivation of DNP, similar to ANP, revealing that NEP is involved in the inactivation of BNP and ANP in the plasma. However, these observations are fairly different from an earlier study, which revealed that DNP was resistant to degradation by NEP (29).…”
Section: Discussionsupporting
confidence: 82%
“…These enzTmes are membrane bound and their active sites face the lumen of the tubule (39). Incubating ANF(99-126) with these kidney microvilli results in a major degradation product cleaved between cysteine and phenylalanine (C'ys 105-Phe 106) (37,38,(40)(41)(42). Since the intact ring structure of ANF(99-126) is essential for its biological activity (43,44), ANF is effectively inactivated by this cleavage process.…”
Section: Enzymatic Dem'adationmentioning
confidence: 99%
“…21,22,35 ANP may also be metabolized by an aminopeptidase, which is insensitive to thiorphan. 61 Although incomplete local NEP inhibition is possible, it is highly unlikely because the doses of both candoxatrilat and thiorphan used were chosen to achieve local blood concentrations in the forearm Ͼ50-fold and Ͼ10-fold higher than the IC 50 of (ϩ)candoxatrilat and thiorphan, respectively, for ANP in vitro. 39 Consistent with earlier work, 62 systemic ACE inhibition with enalapril had no effect on plasma ET concentrations.…”
Section: Discussionmentioning
confidence: 99%